'Upliftment', friends and finance: everyday exchange repertoires and mobile money transfer in Kenya. Issue 4 (26th November 2018) - Johnson, Susan; Krijtenburg, Froukje
Abstract: The rapid and massive adoption of mobile money transfer (MMT) services in East Africa, particularly in Kenya, stands in stark contrast to historically low use of formal financial systems on the continent. Its 'fertile grounds' therefore require in-depth analysis to understand the implications for African financial systems. This paper argues for the need to examine the underlying conceptual environment that enables low income and poor people's MMT adoption. It innovatively combines anthropological with ethnolinguistic analytical approaches to distinguish two repertoires around resource exchange. First, is a relational financial repertoire where relationships are developed and consolidated to create support and 'upliftment'. A contrasting resource-focused repertoire is more like that of the formal financial sector. Identifying the conceptual features of relationality, the study offers a new perspective on the adoption and use of MMT in Africa and highlights the potential for disjunctures with policy efforts to increase financial inclusion.